A Clinical-Psychological Perspective on Somatization Among Immigrants: A Systematic Review - Lanzara, Roberta; Scipioni, Mattia; Conti, Chiara (Frontiers in Psychology, 2019)
Background: Somatic and psychopathological conditions (e.g., anxiety, depression, post-traumatic stress disorder, and somatization) are frequent among immigrants belonging to various ethnic groups. Worldwide findings on the epidemiology regarding specific mental conditions still vary with respect to different migration samples and migration contexts. This inconsistency also holds true in the incidence of somatization among migrants. We carried out a systematic review analyzing the relationship between migration and somatization by providing a qualitative data synthesis of original research articles on the topic. Methods: According to PRISMA guidelines, we conducted a systematic search of the literature on PubMed, Scopus, ISI Web of Science, PsycINFO, Google Scholar, and ScienceDirect. The articles were selected using multiple combinations of relevant search terms (e.g., defined somatization and related disorders, and migration status). Each database was searched systematically from January 2000 to December 2017. Results: The initial search identified 338 records, of which 42 research reports met the predefined inclusion criteria and were analyzed. Most studies (n = 38; 90%) were cross-sectional. The main findings of this study are that migrants with somatization exhibited more psychological distress, had an increased perceived need for healthcare service utilization, and reported more post-migration living difficulties and/or post-traumatic stress disorder than those without somatization. It was also found that specific individual features mediate the association between somatization and migration. The prevalence and correlates of somatization were found to vary across the immigrant groups, depending on cultural variation in reasons for migration, stress exposure, explanatory models of illness, coping, and other individual variables. Conclusion: Somatization is a challenge for health professionals due to its vague nature. In this regard, clinical management of immigrant patients should include further efforts to address emotional distress, with special attention to social, cultural, and linguistic differences.